Monitoring Role And Private Information On Firms’ Internationalisation:The Effects Of Corporate Governance On Executive Compensation. - Lee, Lian Yee (2021)
Executive directors’ compensation consists of two roles, monitoring and private information. Directors are due to perform the monitor role which align with benefits they received. However, private information role which shareholders do not know could lead to the overpaid of executive directors’ compensation. In this study, the first objective is to investigate the effects of monitoring role and private information in executive compensation on firms’ internationalisation in terms of foreign assets (FATA) and sales (FSTS). The second objective looks at the effectiveness of corporate governance mechanisms on monitoring role and private information towards the firm’s internationalisation. While the third objective focuses on the remuneration committee, the last objective addresses the endogenous effects of executive compensation and internationalisation. The study applies the argument of information processing theory, and agency theory to build up hypotheses. To address the issues, a sample consists of 446 public listed firms in Malaysia, from the year 2008 to 2016 are used to examine the hypotheses in the study. The findings indicate that executive directors who receive their compensation do not perform to the best interest of shareholders when pursuing internationalisation. The monitoring role of executive compensation does not positively explain firms’ strategies to go overseas in terms of foreign assets and foreign sales.However, in Malaysia, the presence of private information increases foreign assets (FATA) but reduces foreign sales (FSTS), confirming executive directors pursue their private interest, especially to accumulate assets which may not benefits firms directly. Further investigation found a mixed result of the effectiveness of corporate governance on governing director compensation. The finding indicates the governance mechanism of board size is not effective in governing the monitoring role of executive compensation towards internationalisation.